The Relationship Between Learning Anxiety And Students' Mathematics Learning Difficulties During The Covid-19 Pandemic - Roy, La; Patih, Tandri; Halistin, Halistin; Masdin, Masdin; Syarwa Sangila, Muhammad (International Journal of Transdisciplinary Knowledge, 2022)
This quantitative study aims to determine the relationship between anxiety in learning mathematics and learning difficulties in mathematics for class XI students at SMAN 5 Kendari during the covid-19 pandemic using correlational research methods. Data was collected through online questionnaires using google forms. This study uses a gradual sampling technique. The first stage uses stratified random sampling by considering classes XI MIPA, XI IPS, and XI BB as strata. Then each stratum is calculated using the proportional stratified random sampling formula. Furthermore, in class XI MIPA, cluster random sampling was conducted to select four classes from the six available classes. Again, each selected class will be selected at simple random sampling. This study indicates a significant relationship between students' mathematics learning anxiety and students' mathematics learning difficulties in Class XI SMA Negeri 5 Kendari during the Covid-19 pandemic. The relationship between students' mathematics learning anxiety variables and mathematics learning difficulties is low, and the magnitude of the relationship between mathematics learning anxiety and mathematics learning difficulties in class XI SMAN 5 Kendari using Spearman-rank correlation analysis is 0.329.